ENGLISH LANGUAGE TEACHING METHODS IN PRIMARY EDUCATION - Maxmudov Akbarjon Anvarjon o'g'li; Azzamova Nigora Rajabboyevna (TADQIQOTLAR.UZ, 2024)
This paper investigates various methods of teaching English in primary education, emphasizing the critical importance of establishing a strong foundation in language development at an early age. The study compares different approaches, including interactive and communicative methods, the integration of technology, and the role of student participation in the learning process. By examining the effectiveness of these methods, the research highlights how diverse teaching strategies can enhance language proficiency among young learners. The findings suggest that incorporating a variety of engaging and participatory techniques positively impacts students' language acquisition and overall educational experience.